2015 IEEE 35th International Conference on Electronics and Nanotechnology (ELNANO) 2015
DOI: 10.1109/elnano.2015.7146919
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic heart disease recognition by k-NN classification of current density distribution maps

Abstract: Magnetocardiography is non-invasive and riskfree technique allowing body-surface recording of the magnetic fields generated by the electrical activity of the heart. In this paper, k-Nearest Neighbor algorithm is applied for binary classification of myocardium current density distribution maps (CDDM). Different types of CDDMs from patients with ischemic heart disease are compared with normal subjects. Selection of number of neighbors for k-NN classifier was performed to optimize classification characteristics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In our further study, we developed a multiclass classifier based on correlation analysis ( 9 ), with value of accuracy equal to 95%, in order to provide a tool for the complex analysis of a patient's cardiovascular system by MCG. In other study, we applied a k-NN algorithm for the binary classification of CDDMs for ischemic heart disease recognition ( 10 ). Developed classifiers showed accuracy in the range of 60–90% depending on the type of CDDM.…”
Section: Introductionmentioning
confidence: 99%
“…In our further study, we developed a multiclass classifier based on correlation analysis ( 9 ), with value of accuracy equal to 95%, in order to provide a tool for the complex analysis of a patient's cardiovascular system by MCG. In other study, we applied a k-NN algorithm for the binary classification of CDDMs for ischemic heart disease recognition ( 10 ). Developed classifiers showed accuracy in the range of 60–90% depending on the type of CDDM.…”
Section: Introductionmentioning
confidence: 99%
“…It is more typically used for classification tasks than for regression tasks. Study [23] classified heart disease using KNN. In paper [24], the authors suggested a model for offline handwritten digit prediction using KNN.…”
Section: Instance Based/lazy Learningmentioning
confidence: 99%
“…From the experiment results obtained 80-88% accuracy range, 70-95% sensitivity, 78-95% specification and 77-93% precision. In another research, Udovychenko et al, [21] classified the Ischemic heartbeat using the K-Means method. Based on the results of the experiment, the optimal number of neighbors in increasing accuracy was 20-25 neighbors.…”
Section: Literature Studymentioning
confidence: 99%